(untitled) (Global Journal of Science Frontier Research, 2020)
The rule of this paper is to study a possibility of using Simvastatin pharmaceutical drug compound as corrosion inhibitor that can have a decisive effect of decreasing on metallic corrosion rate and adsorbed on the metal surface by using potentiodynamic polarization and Evans techniques. In this regard, we simultaneously present an overview on Simvastatin compound performance, as corrosion inhibitor in 10% ethanol, 0.5N H 2 SO 4 (10A5H), and with presence different concentration of drug. The potentiodynamic polarization and Evans technique are studied the LCH in different medium to clarify the effect of medium on the corrosion processes and the effect of polarization on the orientation of inhibitor molecule to the metal surface. The surface examination by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and atomic force microscopy (AFM). All surface examinations confirm formation, thin film adsorbed on the metal surface which discussed by the mechanism of the adsorption processes on the polarized metal surface.